2020
DOI: 10.1096/fj.201902013rrr
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholyl lysophosphatidylethanolamide protects against hepatic ischemia/reperfusion injury via phospholipid metabolism‐mediated mitochondrial quality control

Abstract: Mitochondrial dysfunction is the leading cause of reactive oxygen species (ROS) burst and apoptosis in hepatic ischemia/reperfusion (I/R) injury. Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) is a hepatotargeted agent that exerts hepatoprotective roles by regulating lipid metabolism. Our previous studies have shown that UDCA-LPE improves hepatic I/R injury by inhibiting apoptosis and inflammation. However, the role of UDCA-LPE in lipid metabolism and mitochondrial function in hepatic I/R remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In this study, the morphology of hepatocytes revealed that the damage of mitochondria was significantly reduced after ADSCs‐exo treatment. As regard the ATP production our results were consistent with those of previous studies, 35,36 since the ATP content in the liver of the I30R+PH group was significantly lower than that in the Sham group, which might be due to a direct consequence of impaired mitochondrial dynamics. ADSCs‐exo treatment reversed the decrease of ATP content caused by HIRI subsequent to hepatectomy.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the morphology of hepatocytes revealed that the damage of mitochondria was significantly reduced after ADSCs‐exo treatment. As regard the ATP production our results were consistent with those of previous studies, 35,36 since the ATP content in the liver of the I30R+PH group was significantly lower than that in the Sham group, which might be due to a direct consequence of impaired mitochondrial dynamics. ADSCs‐exo treatment reversed the decrease of ATP content caused by HIRI subsequent to hepatectomy.…”
Section: Discussionsupporting
confidence: 92%
“…These fragmented organelles fuse to an interconnected network which renews the damaged mitochondrial DNA (mtDNA) [25]. Excessive fission causes mitochondrial breakage and activates its apoptosis pathway, thus aggravating tissue damage and cell apoptosis [26]. Additionally, excessive fission of mitochondria is a pre-symptom of cytochrome-C (cyt c) release [27], and the release of cyt c further promotes the mitosis of mitochondria.…”
Section: Mitochondrial Fission and Fissionmentioning
confidence: 99%
“…Mitochondrial fusion has long been regarded as a protective way to reduce mitochondrial fission [9]. During hepatic IRI, the fusion of damaged mitochondria could cause a beneficial effect to maintain the survival function of mitochondria [26] by preventing mitochondrial decomposition caused by the release of cyt c, xanthine oxidase (XO), and ROS in mitochondrial [31]. Fusion is associated with the redistribution of metabolites, proteins, and mtDNA in mitochondria.…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytosolic phospholipase A2 (PLA2), a phospholipase, hydrolyzed mitochondrial membrane phospholipids and resulted in mitochondria-mediated oxidative stress and apoptosis. Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) could regulate the crosstalk between the phospholipid metabolism and mitochondria, restore mitochondrial function and alleviate IRI [ 36 ]. During liver IRI, mitochondrial permeability transition pore opening leads to the dysfunction of mitochondria.…”
Section: Acute-phase Inflammation Initiated By Hepatic Irimentioning
confidence: 99%